Quantitative Evaluation of Microstructure of Graphitic Cast Irons - Vaško, Alan; Markovičová, Lenka; Zatkalíková, Viera; Tillová, Eva (Manufacturing Technology Journal, 2014)
The paper deals with some problems of quantitative metallography which includes evaluation of microstructure by etalons, measurement of structural parameters by coherent test grids and automatical image analysis. Some advantages and disadvantages of these methods are shown in this contribution on the example of evaluation of microstructure of graphitic cast irons. The automatical image analysis enables to eliminate some disadvantages of evaluation of microstructure by etalons and by coherent test grids but it has also some negatives.
Keywords: Quantitative metallography; Microstructure; Image analysis; Graphitic cast irons